2021
DOI: 10.7759/cureus.19602
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Associated Coagulopathy Resulting in Cerebral Venous Thrombosis and Pulmonary Embolism

Abstract: Venous stroke is an infrequent complication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease. Coronavirus disease 2019 (COVID-19) acts as a causative factor for thromboembolic events such as pulmonary embolism (PE), deep vein thrombosis (DVT), stroke (ischemic or hemorrhagic), and myocardial infarction. We report a case of cerebral venous thrombosis (CVT) following severe COVID-19 infection, with co-incidence of pulmonary thromboembolism. A 39-year-old English lady presented with fever a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Putative mechanisms include viral neurotropism, a hyperinflammatory and hypercoagulable state, or pathological brain-lung crosstalk (6). Endothelial dysregulation (7)(8)(9) and pro-thrombotic state (10)(11)(12) have been widely suspected to be the possible main contributors of the increased risk of Abbreviations: APELSO, Asia-Pacific extracorporeal life support organization; BMI, body mass index; CNS, central nervous system; COVID-19, Coronavirus disease 2019; CT, computed tomography; ECMO, extracorporeal membrane oxygenation; ECMOCARD, ExtraCorporeal Membrane Oxygenation for 2019 novel Coronavirus Acute Respiratory Disease; eCRF, electronic case report form; ICU, intensive care unit; IRB, institutional review board; ISARIC, International Severe Acute Respiratory and emerging Infection Consortium; MRI, magnetic resonance images; mRS, modified Rankin scale; NSE, neuron specific enolase; PNS, peripheral nervous system. neurologic events.…”
Section: Introductionmentioning
confidence: 99%
“…Putative mechanisms include viral neurotropism, a hyperinflammatory and hypercoagulable state, or pathological brain-lung crosstalk (6). Endothelial dysregulation (7)(8)(9) and pro-thrombotic state (10)(11)(12) have been widely suspected to be the possible main contributors of the increased risk of Abbreviations: APELSO, Asia-Pacific extracorporeal life support organization; BMI, body mass index; CNS, central nervous system; COVID-19, Coronavirus disease 2019; CT, computed tomography; ECMO, extracorporeal membrane oxygenation; ECMOCARD, ExtraCorporeal Membrane Oxygenation for 2019 novel Coronavirus Acute Respiratory Disease; eCRF, electronic case report form; ICU, intensive care unit; IRB, institutional review board; ISARIC, International Severe Acute Respiratory and emerging Infection Consortium; MRI, magnetic resonance images; mRS, modified Rankin scale; NSE, neuron specific enolase; PNS, peripheral nervous system. neurologic events.…”
Section: Introductionmentioning
confidence: 99%
“…Although COVID-19 mainly affects the lungs, many studies have reported various direct or indirect associations between COVID-19 and the occurrence of cerebral infarction. COVID-19 can lead to coagulation dysfunction and inflammation in various patients, promote the disorder of blood clotting function, and thus cause venous thromboembolism and lead to brain infarction [ 31 , 32 ]. Some studies have found that cerebral artery occlusion and infarction occurred in infants with critically ill COVID-19 due to D-dimer elevation and coagulation dysfunction [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective multicenter cohort study that involved 13,500 patients with COVID‐19 reported an incidence of venous stroke of 8.8 per 10,000 over 3 months 199 . Symptoms of COVID‐19 infection are often observed in patients with concomitant SARS‐CoV‐2 infection and venous stroke 200 . In a New York metropolitan cohort study, 13,500 patients with COVID‐19 were enrolled, and 12 patients had venous stroke, with headache being the most common neurological symptom in 85% of patients, focal symptoms such as seizures and hemiparesis were present in 42% of patients, and cortical signs such as aphasia, neglect, or hemianopia were present in 25% of patients 199 .…”
Section: Infection and Vaccination Associated With Venous Strokementioning
confidence: 99%